Analysis of Local Revenue, Revenue Sharing, and General Allocation Funds on Capital Expenditure in North Sumatra - Tirtana, Dodi; Pradani, Tiara; Aulia, Nadia; Aryanti, Silvia Dwi; Sihite, Indah Elyza (Jurnal Akuntansi, 2024)
This study aims to analyze how factors are affect on capital expenditures in the Regency / City of North Sumatra. Local own-source revenue, revenue-sharing funds, and general allocation funds are to be independent variables while capital expenditure is the dependent variable. This study uses panel data obtained from the Indonesian Ministry of Finance in 2022-2023. The analysis method in this study uses panel data regression with the Fixed Effect Model (FEM) approach. The results showed that simultaneously the variables of local revenue, revenue-sharing funds, and general allocation funds had a significant influence on capital expenditure. Based on partial testing, only the revenue-sharing variable has significant negative effect on capital expenditure. These results imply that more effective strategies in the use of revenue-sharing funds need to be developed, such as increasing transparency and adjusting fund allocation policies in supporting capital expenditures. The results of this study can assist governments in planning budgets more effectively, identifying the most influential financial resources, and adjusting spending strategies to maximize the efficient use of funds. Translated with www.DeepL.com/Translator (free version) Keywords: Local own-soruce Revenue, Revenue-Sharing Fund, General Allocation Fund, Capital Expenditure